(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Background. Radical cystectomy remains the gold standard for the treatment of muscle-invasive bladder cancer (MIBC). However, the choice of urinary diversion has a significant impact not only on surgical outcomes but also on long-term quality of life (QoL).